Characterization of silicide phases formed during pack siliconizing coating on the Nb-1Zr-0.1C alloy. (August 2015) - Vishwanadh, B.; Majumdar, S.; Orsborn, J.; Banerjee, R.; Tewari, R.; Fraser, H.; Dey, G.K.
Abstract: The present paper describes the morphology, chemistry and crystallography of the phases observed in the silicide coatings produced by pack cementation technique on Nb based alloys. Cross-sectional microstructures examined by transmission electron microscopy and scanning electron microscopy techniques have shown that the coating has two silicide layers: NbSi2 and Nb5 Si3 . NbSi2 formed at the surface of the sample and Nb5 Si3 formed in between the substrate (Nb alloy) and NbSi2 coating layer. Electron diffraction analyses revealed that NbSi2 has hexagonal crystal structure with lattice parameters as a = 0.48 nm and c = 0.66 nm and Nb5 Si3 has tetragonal crystal structure with lattice parameters as a = 0.65 nm and c = 1.19 nm. Nb5 Si3 showed fine equiaxed grains, whereas, NbSi2 exhibited duplex morphology having columnar grain morphology near to the Nb5 Si3 layer and large equiaxed grains at the surface of the coating sample. The presence of duplex morphology was explained by estimating diffusion of various species and it was shown that columnar morphology of grains could be attributed to outward diffusion of Nb and equiaxed grains to inward diffusion of Si. In the case of Nb5 Si3, growth takes place due to single element Si diffusion, leading to development of single equiaxed grain morphology of the Nb5 Si3 phase. Highlights: Microstructure of the silicide coating produced by pack cementation technique on Nb-1Zr-0.1C alloy was characterized. The coating had two silicide layers: NbSi2 and Nb5 Si3 . Crystal structure of the NbSi2 and Nb5 Si3 was determined. Formation mechanism of the silicide coating layer has been explained by diffusion.